Pengaruh Komunikasi Internal Terhadap Kinerja Pegawai Di Satuan Kerja Lalu Lintas Polresta Samarinda - Aliani, Ardia; ., Jubaidi; Efendi, Achmad (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of internal communication on employee performance at the Traffic Unit of Polresta Samarinda. The main problem addressed is the lack of effective internal communication, which leads to miscommunication, task execution errors, and low employee morale. This research uses a quantitative approach with a survey method involving 93 respondents out of a total population of 120 employees. Data were collected through questionnaires, and the validity and reliability were tested using SPSS version 27. The data analysis techniques used include simple linear regression, t-test, and the coefficient of determination. The results show that internal communication has a positive and significant effect on employee performance, with a regression coefficient value of 0.810 and a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) value of 0.748 indicates that 74.8% of the variation in employee performance can be explained by internal communication, while the remaining 25.2% is influenced by other factors. These findings emphasize the importance of effective internal communication in improving employee performance, especially in work environments that require high levels of coordination, such as the police force. Therefore, improving the quality of internal communication can be a key strategy to enhance work effectiveness and productivity in the Traffic Unit of Polresta Samarinda.